THE VALUE OF CITIZEN JOURNALISM IN NEWS PRODUCTON - Willson Gustiawan, Lin Tay Jou, Richad Yanato (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
The purpose of this research is to find how the role of citizen journalists in news program NET 10 as one of the programs NET TV whose typical citizen journalism characteristic. As known that NET TV is television that follows the concept of citizen journalism since establishing in may 2013. This research using descriptive study to explore news website NET CJ on news program in NET 10. Qualitative methods by using in-depth interviews was conducting with four source. They are NET TV news producer, and citizen journalists. The results of the study concluded that citizen journalist is one of an element of which is very important in preaching the news, although most of citizen journalist do not come from journalist background. Citizen journalist having a different point of view which is not possessed professional journalist. Keywords: citizen journalism, news media